The Neolithic Bone Items of the Lower Volga Region - Anna A. Malyutina; Aleksandr A. Vybornov; Tatiana Yu. Grechkina (Археология евразийских степей)
Late Stone Age sites in the semi-desert and steppe zones of Russia with preserved items made of bone, antler or teeth, for various reasons, have been poorly studied. Nevertheless, it is obvious that artifacts of both a household and non-utilitarian character made of these raw materials played a major role in the life of the ancient Neolithic population of the area under consideration. This is proved by the materials of the Kairshak III and Varfolomeevskaya campsites, where bone artifacts were found for the first time. Systematic archaeological studies in the Lower Volga region in recent decades have revealed a number of multi-layered and single-layered Neolithic settlements. Among them, the Algai and Priozernaya sites are of great interest for studying both the periodization of the region’s cultures and their economic and everyday life. The discovered bone artifacts (13 items) made it possible to get qualitatively new information using typological and traceological analysis. Both peculiarities and specific features for each site have been identified. The ways of their manufacture have been determined.